Depression, anxiety, and stress in the Chilean Educational System: children and adolescents post-pandemic prevalence and variables - Martínez-Líbano, Jonathan; Yeomans-Cabrera, María-Mercedes (Frontiers in Education, 2024)
The mental health of children and adolescents in the Chilean Educational System (ChES) has become a severe post-pandemic public health problem. This cross-sectional study, which included 1,174 children and adolescents from five Chilean regions, used the DASS-21 scale, focusing on determining the prevalence of depression, anxiety, and stress, as well as identifying associated risk factors. The results exposed a high prevalence of depression, anxiety, and stress (60.2%, 63.6%, and 50.2%, respectively). Risk factors for depression involve being female, having separated parents, being in high school, having a cell phone, difficulty sleeping, ruminative thoughts, and low self-esteem. For anxiety, factors included being female, being 12 years old, owning a cell phone, having sleep problems, having ruminations, having low self-esteem, and being an atheist. For stress, factors were identified as being female, owning a cell phone, sleep problems, ruminations, low self-esteem, being atheist, as well as extensive use of social networks. The research underscores the urgent need for intervention by educational authorities, given the marked deterioration in the mental health of children and adolescent students in the ChES, to prevent long-term consequences.